Judicial Commission Supervision in the Relations with the Authority of the Supreme Court (International Journal of Scientific Research and Management (IJSRM), 2019)
The Judicial Commission is formed with two constitutive authorities, namely to propose the appointment of Supreme Judges and have other authority in order to maintain and uphold the honor, dignity and behavior of judges. This study will focus on knowing and analyzing the implementation of the roles and functions of Judicial Commission in maintaining the dignity of judges and to know more deeply about the continuity and strength of sanctions, especially moderate and mild sanctions issued by Judicial Commissions on judges who violate the Code of Ethics and Judicial Behavior Guidelines (KE&PPH) so many proposed recommendations for sanctions of the Judicial Commission are exceute by the Supreme Court of Justice as the executor of sanctions and what are the legal consequences of this act.